Modern view on a problem «children with recurrent infections» (frequently ill children) and their immune status - M. A. Kazumian; A. V. Vasilenok; E. D. Teplyakova (Медицинский вестник Юга России, 2018)
The article presents the review of the domestic and international researches devoted to one of the most «problem» aspects of pediatrics – to patients with recurrent infections (frequently ill children) and to their immune status (an immune imbalance). Children with recurrent infections (frequently ill children) are characterized by higher, than their peers, incidence of acute respiratory infection (ARI). ARI frequency up to 8 times a year can be a normal variant at favorable course, at the same time an immune imbalance is compensated by immune system.